2016
DOI: 10.1016/j.watres.2015.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Microcystis aeruginosa using cationic starch modified soils

Abstract: a b s t r a c tA cheap and biodegradable modifier, cationic starch (CS), was used to turn local soils into effective flocculants for Microcystis aeruginosa (M. aeruginosa) removal. The isoelectric point of soil particles was remarkably increased from pH 0.5 to 11.8 after modification with CS, which made CS modified soil particles positively charged and obtain algal flocculation ability. At the soil concentration of 100 mg/L, when the CS modifier was 10 mg/L, 86% of M. aeruginosa cells were removed within 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 47 publications
0
44
0
Order By: Relevance
“…Most of geo-engineering materials so far only focus on the P reduction. The MLS materials (Li and Pan, 2013;Shi et al, 2016;Zou et al, 2006) can simultaneously manipulate N and P by removing algal blooms in short term, affecting redox environment in the sediment, and restoring submerged vegetation in long term in shallow waters (Pan et al 2011(Pan et al , 2012a. High water clarity and the low nutrient concentrations can be quickly obtained by MLS flocculation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of geo-engineering materials so far only focus on the P reduction. The MLS materials (Li and Pan, 2013;Shi et al, 2016;Zou et al, 2006) can simultaneously manipulate N and P by removing algal blooms in short term, affecting redox environment in the sediment, and restoring submerged vegetation in long term in shallow waters (Pan et al 2011(Pan et al , 2012a. High water clarity and the low nutrient concentrations can be quickly obtained by MLS flocculation.…”
Section: Discussionmentioning
confidence: 99%
“…Once positive charges were overdosed, the removal efficiency decreased, since the reversal of cell surface charge (Fig. 2b) potentially reintroduced the electrostatic repulsion and prevented aggregation between CS-MS and algae particles (Jangkorn et al, 2011;Mosse et al, 2012;Shi et al, 2015). Hence, to achieve effective algal removal using MSs, the modifier loading mainly depended on the charge density.…”
Section: Charge Density and The Optimal Dosage Of Csmentioning
confidence: 99%
“…Modified soils (MSs) have triggered great interest as geo-engineering materials for cyanobacterial bloom control in recent years (Lürling and van Oosterhout, 2013;Mackay et al, 2014;Spears et al, 2014;Tian et al, 2014). Although many studies on algal removal using MSs have been reported (Li and Pan, 2013;Pan et al, 2011a;Shi et al, 2015;Zou et al, 2005), little is known about its potential impacts on the receiving waters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations